Exits from the European Union and their effect on power distribution in the council - Dóra Gréta Petróczy; Mark Francis Rogers; László Á. Kóczy (Games, 2022)
Debates on an EU-leaving referendum arose in several member states after Brexit. We want to highlight how the exit of an additional country affects the power distribution in the Council of the European Union. We inspect the power indices of the member states both with and without the country which might leave the union. Our results show a pattern connected to a change in the number of states required to meet the 55% threshold. An exit that modifies this number benefits the countries with high population, while an exit that does not cause such a change benefits the small member states. According to our calculations, only the exit of Poland would be supported by the qualified majority of the Council.
Keywords: 330; Brexit; European Union; power index; qualified majority voting